PENERAPAN MODEL PEMBELAJARAN LEARNING COMMUNITY BERBASIS MEDIA SOSIAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Rustiyono Rustiyono (Universitas Muhammadiyah Bengkulu, 2020)
The purpose of this study was to determine an effect of the application of the social media-based learning community learning model on the learning outcomes of class XII students of SMA Negeri 7 Bengkulu for the 2018/2019 academic year. The research method used is a pure experimental method with a research design form Posttest Only Control Design. The T-test results obtained by an average attitude assessment learning result are as follows: the value of spiritual attitudes between the experimental class and the control class assuming homogeneous data (Equal variances assumed) is obtained a sig. (2-tailed) value of 0.000 <0.05, with tcount = 6.652> 1.668 = ttable (0.05: 67). Assessment of social attitudes obtained a sig. (2-tailed) value of 0,000 <0.05, with tcount = 3,742> 1,668 = ttable (0.05: 67). Comparison of the average learning outcomes of the knowledge value with the assumption of homogeneous data, the sig. (2-tailed) value is 0.000 <0.05, with tcount = 5.477> 1.669 = ttable (0.05: 65). While the assessment of skills obtained a sig. (2-tailed) value of 0.002 <0.05, with t = 2.469> 1.668 = ttable (0.05: 67). Based on the results of data analysis, it was concluded